ANALISIS RETAILMIX DAN VARIAN PRODUK TERHADAP MINAT BELI PADA SUPERMARKET BOLLYMARTKABUPATEN BIMA - Nurhayati Nurhayati; Muhajirin Muhajirin (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract: This study aims to examine the effect of retail mix which consists of service, pricing, location, products, promotion, communication, and product variants on buying interest in Bollymart, Bima Regency, either partially or simultaneously. This type of causal associative research with quantitative methods. The population in this study are all consumers who have ever come and shopped at Bollymart. The sampling technique in this study was carried out by purposive sampling technique with a sample of 100 people. The data collection instrument used a questionnaire with a Likert scale that has been tested and has met the validity and reliability requirements. The analytical method used is the classical assumption test and multiple linear regression. Based on the calculation results, it is known that the marketing mix has a significant effect on buying interest at the Bollymart Supermarket with a significance level of P-Value 0.000 <0.05 and product variants have a significant effect on buying interest with a P-Value significance level of 0.004<0.05. Retail mix and product variants simultaneously or jointly have a positive and significant effect on buying interest at the Bollymart Supermarket, Bima Regency with a calculated F value > Ftable, which is 25.891> 3.09 at a significance level of P-Value 0.000 <0.05.